Management of Facilities and Infrastructure to Enhance Student Satisfaction FITK UIN Sunan Kalijaga Yogyakarta - Fuad Fathanah; Na'imah Na'imah; Abdul Aziz (UMSU, 2026)
Management of educational facilities and infrastructure is a fundamental component of higher education that directly contributes to the quality of the learning process and the satisfaction of students as the primary users of campus facilities. This study aims to analyze the current state of facilities and infrastructure management at the taculty of tarbiyah and teacher training UIN Sunan Kalijaga Yogyakarta, to analyze the factors contributing to this situation and to analyze its implications for students learning experiences and satisfaction. The study employs a qualitative approach using a case study design. The informants were selected through purposive sampling and consist of five current students from the FITK UIN Sunan Kalijaga Yogyakarta. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model and supported by source triangulation. The research results identified three main findings. First, the availability of tangible components is sufficiently adequate, but the consistency of their management still requires strengthening. Second, there are three contributing factors: reactive maintenance patterns, disparities in attention between buildings and units, and the suboptimal follow up on the results of periodic satisfaction surveys. The third finding is that these conditions imply that the learning process has not been maximized and lead to strategic recommendations from students regarding the importance of a transparent and responsive infrastructure roadmap. This study concludes that transforming management from reactive to proactive and participatory is a priority for the sustainable development of the Faculty of Tarbiyah and Teacher Training at UIN Sunan Kalijaga